Transformation of Financial Control and Audit of Agricultural Enterprises During the Wartime Period - Drymanova, Lydmyla; Fedoryshynа, Lidiіa (Актуальні питання економічних наук, 2026)
The article examines the peculiarities of the transformation of financial control and audit systems in agricultural enterprises under wartime conditions. The main challenges affecting the financial stability of agricultural enterprises are identified, including economic instability, military risks, disruption of logistics chains, inflationary processes, shortage of financial resources, and growing threats to economic security. The necessity of adapting financial control and audit systems to modern crisis conditions is substantiated. The study reveals the role of a risk-oriented audit approach, digitalization of financial monitoring, and improvement of internal control in ensuring effective management of agricultural enterprises. It is proved that the implementation of digital technologies, automated accounting systems, and modern financial monitoring tools contributes to increasing the transparency of financial reporting, improving the efficiency of managerial decision-making, and minimizing financial risks. Particular attention is paid to the adaptation of internal and external audit procedures to conditions of wartime instability. The main directions for improving financial control aimed at strengthening economic security, ensuring financial stability, and increasing the effectiveness of anti-crisis management of agricultural enterprises are determined. As a result of the study, the necessity for a comprehensive transformation of financial control and audit systems based on the combination of risk-oriented management, digital technologies, and adaptive financial monitoring mechanisms is substantiated. The practical significance of the obtained results lies in the possibility of their application for improving financial management and ensuring sustainable development of the agricultural sector under conditions of prolonged economic and military instability.